Economic impact of international labour migration on Lesotho's development, 1986-1998: towards an international labour migration policy for the Southern African region - Maro, Mkasafari Grace (Rhodes University, Faculty of Commerce, Department of Economics, 2002)
The aim of the thesis is to identify the pressures that contributed to the rise in international labour migration in Lesotho, and to investigate how these pressures are impacting upon the modernization process in the country, particularly at a time when employment opportunities are scarce in the southern African region. International labour migration has been used as a development tool throughout history, but especially in the 20th century by developing countries with dual labour markets. Newly independent developing countries with dual labour markets adapted the strategy of import substitution industrialization (lSI), with an emphasis on protecting infant industries and promoting pro-labour policies. In the post-colonial period the international demand for lowskilled workers rose, particularly in the North (developed countries), and in mineral rich countries including the oil exporters and South Africa, and the newly industrialising countries in East Asia. International labour migration to these countries was adapted as an integral development tool by the governments of the lSI countries. Most migrants were low-skilled and temporary workers in the destination countries. Although no multilateral institutional framework existed, usually both the sending and receiving countries adapted unilateral and bilateral migration policies to guarantee the gains from migration. Workers were thus "protected" to varying degrees under such agreements. From the 1970s, the North experienced a slowdown in the growth in demand for unskilled workers. In the 1980s, many lSI countries experienced devastating economic crises that forced them to abandon the lSI policy and adapt the export-led industrialisation (EOI) policy with an emphasis on trade liberalization. The switch from lSI to EOI in developing countries with dual labour markets led to the downsizing of public sector employment, the removal of marketing boards formally used by small-scale agricultural farmers, and the expansion of export processing zones (EPZs). These outcomes resulted in a rise in push internal migration, and international migration from these countries especially to other developing countries. At the same time, since the late 1980s, capital has acquired greatly enhanced mobility at the global level. The adaptation of EOI and the full mobility of capital at the global level altered the institutional structure within which labour migration was governed both nationally, and internationally. At the national level stricter unilateral policies were reinforced by receiving countries for low-skilled labour, while less strict policies applied for skilled labour. These remain in operation in conjunction with the earlier bilateral agreements. At the international level, there remains a lack of policy to regulate international labour migration. Under the current enhanced mobility of capital, international migrants are thus left vulnerable. Lesotho fits this pattern. Faced with a dual economy and an abundance of semi-skilled labour, Lesotho has been a principal supplier of labour to the South Africa's mining industry since its independence. Lesotho's industrial diversification thus mirrors South Africa's industrial diversification. In the lSI phase (1968 - 1987), international labour migration became the most important tool of economic welfare generation in Lesotho. Bilateral agreements were signed in the early 1970s between Lesotho and South Africa to guarantee the gains from migration. Since the late I980s, the mining industry in South Africa began to downsize production and employment. Fewer novice miners from Lesotho were recruited to work in South Africa. The adaptation of the EOI policy in Lesotho in 1987 introduced EPZ industrialization and trade liberalization. Nevertheless, the retrenchment of mine workers from South Africa is occurring at a time when Lesotho is experiencing an employment crisis. The political independence of South Africa in 1994 was accompanied by stricter international migration policies by the new democratic government of South Africa. Most migrant workers in South Africa are thus now faced with a two-door policy (of the earlier bilateral agreements and the amendments to the Aliens Control Act). This system has left migrant workers vulnerable to exploitation by both employers and the law (police) in South Africa. Nevertheless, international migration from Lesotho to South Africa continues to expand, particularly of the new type of migration - semiskilled female workers in the services sector. At the same time, South Africa is also experiencing an employment crisis. The most important policy implications are, firstly, that migration is subject to the same "casualisation" as other work, with the effects made worse by the "statelessness" of migrants, who are most vulnerable to exploitation. Secondly, multilateralism is needed (e.g., SADC) and holistic, multilateral policies are required. It is clear that under the new global division of labour ad hoc policy towards international labour migration is ineffective.
Keywords: Migrant labor -- South Africa; Migrant labor -- Lesotho; Foreign workers -- South Africa; Miners -- South Africa; Miners -- Labor unions -- South Africa